Obesity and risk of hypertension in preadolescent urban school children: insights from Pakistan - Samina Akhtar; Shahid Khan; Namra Aziz; Muhammed Imran; Zainab Samad; Romaina Iqbal; Aysha Almas (BMC, 2024)
Abstract Background Childhood obesity and hypertension are growing concerns globally, especially in developing countries. This study investigated the association between overall and central obesity at baseline, and prehypertension or hypertension at follow-up among preadolescent school children in urban Karachi, Pakistan. Methods This is a sub study with cohort design embedded within a feasibility trial on School Health Education Program in Pakistan (SHEPP) in preadolescents aged 6-11 years, attending two private schools conducted from 2017 to 2019. Hypertension or prehypertension at follow-up were the outcomes and obesity or central obesity at baseline were the exposure variables. Hypertension was defined as systolic blood pressure and/or diastolic blood pressure ≥ 95th percentile for age, sex, and height. Obesity was defined as body mass index for-age and sex ≥ 95th percentile, whereas central obesity was determined by waist circumference measurements ≥ 85th percentile of age, sex, and height specific cut-offs. Logistic regression analysis was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs) to identify risk factors for hypertension and prehypertension. Results Analysis was conducted for 908 participants, evenly distributed with 454 boys and 454 girls. Hypertension was observed in 19.8% of the preadolescents, with rates of 18.5% in boys and 21.0% in girls. Prehypertension was found in 16.8% of preadolescents, with 18% among boys and 16% among girls. Additionally, 12.8% of preadolescents were classified as obese and 29.8% had central obesity. Obesity at baseline was associated with hypertension at followup (OR 8.7, 95% CI 3.5, 20.4) in the final model after adjusting for age, gender, physical activity, sedentary behavior, fruits, vegetable intake and hypertension at baseline. Central obesity at baseline also yielded high odds, with prehypertension (OR 1.9, 95% CI 1.4, 2.8) and hypertension (OR 2.7, 95% CI 1.9, 3.9) at follow up in the final model. Conclusion This study highlights a concerning prevalence of hypertension and prehypertension among preadolescent school-going children. Obesity and central obesity at baseline emerged as significant predictive factors for hypertension or prehypertension at followup within this cohort. The findings emphasize the urgency of implementing comprehensive school health education programs aimed at early detection and effective management of hypertension during childhood and adolescence in school settings.